PENERAPAN METODE RESITASI DALAM MENINGKATKAN PEMAHAMAN SISWA MELALUI TUGAS MANDIRI DI LUAR JAM PELAJARAN - Faizatul Widat; Riskiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the recitation method in improving students' understanding of Fiqh subjects in class V of MI Nurul Yaqin. The recitation method is applied through the assignment of independent assignments to students outside of class hours which are then accounted for in class. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects are 20 students in class V and teachers of Fiqh subjects. The results of the study show that the application of the recitation method is able to increase students' understanding of Fiqh material. Students become more able to explain, remember, and apply the material in daily life. In addition, the recitation method also increases students' activeness, independence, and responsibility in the learning process. The supporting factors in this study include the role of teachers, parental involvement, and the availability of learning resources, while the inhibiting factors are differences in students' abilities and the conditions of the learning environment at home. Thus, it can be concluded that the recitation method is effective in improving students' understanding of Fiqh subjects at Madrasah Ibtidaiyah. This method not only improves the cognitive aspect, but also the affective and psychomotor aspects of students through directed independent learning.